2022
DOI: 10.1038/s41467-022-34235-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-healable printed magnetic field sensors using alternating magnetic fields

Abstract: We employ alternating magnetic fields (AMF) to drive magnetic fillers actively and guide the formation and self-healing of percolation networks. Relying on AMF, we fabricate printable magnetoresistive sensors revealing an enhancement in sensitivity and figure of merit of more than one and two orders of magnitude relative to previous reports. These sensors display low noise, high resolution, and are readily processable using various printing techniques that can be applied to different substrates. The AMF-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In addition, self-healing materials have been engineered to autonomously repair mechanical damage, thereby enhancing the overall durability and longevity of the flexible electronics. While substantial progress has been achieved in the development of functional self-healing materials, including proximity sensors, [132] and humidity sensors, [133,134] magnetic field sensors, [135] self-healable sensors face many challenges for practical applications. Typically, the performance of self-healable materials and sensors lags behind that of their non-self-healing counterparts, and most devices that include self-healing materials simply demonstrate functionality.…”
Section: Damage Insensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, self-healing materials have been engineered to autonomously repair mechanical damage, thereby enhancing the overall durability and longevity of the flexible electronics. While substantial progress has been achieved in the development of functional self-healing materials, including proximity sensors, [132] and humidity sensors, [133,134] magnetic field sensors, [135] self-healable sensors face many challenges for practical applications. Typically, the performance of self-healable materials and sensors lags behind that of their non-self-healing counterparts, and most devices that include self-healing materials simply demonstrate functionality.…”
Section: Damage Insensitivitymentioning
confidence: 99%
“…Sensors such as AMR and GMR have already been validated. [135][136][137][138][139] In particular, in Ref, [93] Ha et al have demonstrated a stretchable highperformance magnetic field sensor relying on the GMR effect, which has a high sensitivity within 1 mT, and resists mechanical deformation of up to 16 μm of bending radii and 100% stretching.…”
Section: Mass Productionmentioning
confidence: 99%
“…We envision that this problem can be solved by applying printing technologies that enable the incorporation of Fe nano‐ and micro‐particles within biocompatible and biodegradable matrices while using suitable chemical approaches to prevent Fe oxidation and establish electrical percolation in the printed composite. The use of self‐healing approaches based on alternating magnetic fields [ 282 ] also seems to be advantageous for improving the electrical performance of such devices. Magnetic‐field‐based sensors could be a particularly useful component of wireless implantable healthcare monitoring devices.…”
Section: Challenges and Future Perspectives Of Biodegradable Sensors ...mentioning
confidence: 99%
“…Another approach to bring damaged parts into contact autonomously involves applying magnetic forces. The magnetic force may be generated by an external magnetic source, 308,309 or be based on the inherent attraction between hard magnetic particles. 310,311 Garica-Gonzalez et al proposed a concept for autonomous self-healing MREs by embedding hard magnetic particles in a sticky ultra-soft elastomer matrix.…”
Section: Self-healing Actuatorsmentioning
confidence: 99%